Initial Opening of the Eurasian Basin, Arctic Ocean - Berglar, Kai; Franke, Dieter; Lutz, Rüdiger; Schreckenberger, Bernd; Damm, Volkmar (Frontiers in Earth Science, 2016)
Analysis of the transition from the NE Yermak Plateau into the oceanic Eurasian Basin sheds light on the Paleocene formation of this Arctic basin. Newly acquired multichannel seismic data with a 3600 m long streamer shot during ice-free conditions enables the interpretation of crustal structures. Evidence is provided that no major compressional deformation affected the NE Yermak Plateau. The seismic data reveal that the margin is around 80 km wide and consists of rotated fault blocks, major listric normal faults, and half-grabens filled with syn-rift sediments. Taking into account published magnetic and gravimetric data, this setting is interpreted as a rifted continental margin, implying that the NE Yermak Plateau is of continental origin. The transition from the Yermak Plateau to the oceanic Eurasian Basin might be located at a prominent basement high, probably formed by exhumed mantle. In contrast to the Yermak Plateau margin, the North Barents Sea continental margin shows a steep continental slope with a relatively abrupt transition to the oceanic domain. Based on one composite seismic line, it is speculated that the initial opening direction of the Eurasian Basin in the Arctic Ocean was highly oblique to the present day seafloor spreading direction.